1,8-cineol attenuated Aβ25-35-induced neuron injury through inhibiting IL-6, IL-8 release and NF-κB expression - Lu, Changliang; Wang, Lin; Wang, Shumei; Li, Wanzhong; Li, Haijian; Sun, Lin; Shi, Wenzhen; Zhao, Chunzhen (Journal of Biomedical and Pharmaceutical Research, 2019)
Objective: To explore the protective effect of 1,8-cineol against Amyloid beta25-35 ( Aβ25-35)-induced cell injury in primary rat cortical neurons. Methods: Primary rat cortical neurons were cultured in vitro, treated with different concentrations of Aβ25-35 (2.5, 5, 10 20, 40 μM) and 1,8-cineol (1, 3, 10 μM). Cell viability of neuronal cells were detected by MTT assay and cell death were detected by lactate dehydrogenase release (LDH). The production of IL-6 and IL-8 in the supernatant were measured by ELISA assay kits. NF-κB protein expression was detected by Western blotting. Results: In primary cultured neurons, Aβ25-35 concentration dependently reduced cell viability and increased LDH release. 1,8-cineol with concentrations of 3 and 10 μM protected neuronal cells against Aβ25-35 induced cell injury for 24 h. 3 and 10 μM of 1,8-cineol also significantly decreased the levels of IL-6 and IL-8 cytokine production in the supernatant. Increased NF-κB expression was also significantly reduced by 1,8-cineol treatment evaluated by Western blotting. Conclusions: Our results revealed a protective effect of 1,8-cineol on Aβ25-35 induced neuron injury through inhibition of IL-6, IL-8 production and NF-κB expression.